2017
DOI: 10.3390/ijerph14020199
|View full text |Cite
|
Sign up to set email alerts
|

Thermophilic Fungi to Dominate Aflatoxigenic/Mycotoxigenic Fungi on Food under Global Warming

Abstract: Certain filamentous fungi produce mycotoxins that contaminate food. Mycotoxin contamination of crops is highly influenced by environmental conditions and is already affected by global warming, where there is a succession of mycotoxigenic fungi towards those that have higher optimal growth temperatures. Aflatoxigenic fungi are at the highest limit of temperature although predicted increases in temperature are beyond that constraint. The present paper discusses what will succeed these fungi and represents the fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
45
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 53 publications
0
45
0
1
Order By: Relevance
“…Several factors can influence the presence of mycotoxin in foods and feed such as fungal strain specificity, fungal strain variation, and toxin stability [14][15][16]. However, its occurrence is closely related to environmental conditions favorable to fungal growth, in particular, a hot and humid climate, i.e., mycotoxins are most frequent in tropical areas but they can also be found in a temperate climate [17,18]. Besides that, the mycotoxin contamination may also occur at various stages of the food production chain, e.g., in the storage, in the field, during harvest, processing, and distribution [19].…”
Section: Introductionmentioning
confidence: 99%
“…Several factors can influence the presence of mycotoxin in foods and feed such as fungal strain specificity, fungal strain variation, and toxin stability [14][15][16]. However, its occurrence is closely related to environmental conditions favorable to fungal growth, in particular, a hot and humid climate, i.e., mycotoxins are most frequent in tropical areas but they can also be found in a temperate climate [17,18]. Besides that, the mycotoxin contamination may also occur at various stages of the food production chain, e.g., in the storage, in the field, during harvest, processing, and distribution [19].…”
Section: Introductionmentioning
confidence: 99%
“…Aflatoxins and fumonisins are two major groups of mycotoxins produced by the Aspergillus and Fusarium genera of fungi respectively. These naturally occurring toxins frequently contaminate maize, mainly in countries with high temperature and humidity (Paterson and Lima 2017). Several studies have demonstrated these mycotoxins as potential risk to human and animal health (Wu et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Paterson and Lima [44] considered the effect of global warming on the presence of fungi on food and considered that thermotolerant and thermophilic fungi may dominate by succession over mesophilic fungi. A. fumigatus was considered the greatest risk from this perspective.…”
Section: Resultsmentioning
confidence: 99%